Harnessing Local Wisdom for Sustainable Economic Development: The Case of Bali - Ni Made Suarminiati; I Nyoman Subanda (Green Publisher Indonesia, 2025)
By 2045, Indonesia aims to become the fourth-largest economy in the world, with a projected value of USD 8.89 trillion. Achieving this target requires integrating local wisdom into economic strategies, reflecting the nation’s cultural heritage and sustainability goals. This study examines the gap between these national aspirations and ground realities, focusing on the role of local wisdom in supporting sustainable economic growth. Using a combination of literature review, secondary data, and interviews with key informants, the research explores the role of the “Tri Hita Karana” philosophy, which emphasizes harmony between humans, nature, and spirituality, as a foundation for economic development. The findings indicate that, despite government policies such as the Regional Action Plan for Bali and green economic initiatives that align with local traditions, significant challenges remain, including regulatory inconsistencies, coordination gaps, limited access to capital, and human resource shortages, which hinder effective policy implementation. The study also emphasizes the importance of aligning national strategies with local potential, particularly in regions like Bali, where the creative economy is closely linked to cultural heritage. Unlike previous studies, this research provides a comprehensive analysis of how local wisdom can bridge the gap between policy ambitions and on-the-ground realities, offering practical recommendations to strengthen MSMEs, attract investment, and support the green economy. This approach enhances the competitiveness of local economies while preserving cultural identity.